2023
DOI: 10.1186/s13643-023-02175-8
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of risk factors for mortality among tuberculosis patients in South Africa

Abstract: Background Tuberculosis (TB)-associated mortality in South Africa remains high. This review aimed to systematically assess risk factors associated with death during TB treatment in South African patients. Methods We conducted a systematic review of TB research articles published between 2010 and 2018. We searched BioMed Central (BMC), PubMed®, EBSCOhost, Cochrane, and SCOPUS for publications between January 2010 and December 2018. Searches were con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 51 publications
(171 reference statements)
0
6
0
Order By: Relevance
“…Additionally, it is important to highlight that PTB mortality and DALYs had an upward trend in the past 15 years in Guizhou, primarily due to the continuous increase in deaths from other causes over the same period. Death from other causes in PTB patients might be caused by adverse drug effects [ 49 ] and common comorbidities, such as TB-DM (diabetes mellitus) [ 50 ], TB-HIV positivity [ 51 ] and other age-associated comorbidities [ 49 ]. Therefore, our findings suggest that reducing the TB disease burden in Guizhou will require a multipronged approach, including health system strengthening, integration of TB and common comorbidity services, and person-centered approaches to support treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it is important to highlight that PTB mortality and DALYs had an upward trend in the past 15 years in Guizhou, primarily due to the continuous increase in deaths from other causes over the same period. Death from other causes in PTB patients might be caused by adverse drug effects [ 49 ] and common comorbidities, such as TB-DM (diabetes mellitus) [ 50 ], TB-HIV positivity [ 51 ] and other age-associated comorbidities [ 49 ]. Therefore, our findings suggest that reducing the TB disease burden in Guizhou will require a multipronged approach, including health system strengthening, integration of TB and common comorbidity services, and person-centered approaches to support treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results have been reported in other studies. Low income [ 29 ] and illiterate schooling [ 32 ], previous TB treatment [ 30 , 31 , 51 ]and the use of DOT during the entire treatment [ 55 ] were independently associated with death in TB patients. A possible explanation for the correlation between DOT and death was that DOT was utilized by providers according to decreased social support or increased severity of illness [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two-year mortality was substantial within both cohorts, 22% and 20% in the ethionamide and linezolid cohort, respectively. This may be reflective of a population with high rates of comorbidity, including HIV and high rates of previous TB treatment, both factors associated with poorer outcomes and challenges with regimen adherence [ 24 ]. It is important to note it is not possible to distinguish mortality due to treatment from other causes within this data set.…”
Section: Discussionmentioning
confidence: 99%
“…[ 20 ] reported that the mortality among TB patients was higher in older subjects, and in those with a high comorbidity index. In addition, HIV infection remains a major risk factor for TB mortality in our COVID-19 co-infected cohort [ 21 , 22 ]. As expected, the likelihood that a person with TB would die was significantly higher if they needed invasive ventilation [ 24 ].…”
Section: Discussionmentioning
confidence: 99%